Occupational allergic contact dermatitis and major allergens in France: temporal trends for the period 2001–2010. (1st December 2014) - Bensefa‐Colas, L.; Telle‐Lamberton, M.; Paris, C.; Faye, S.; Stocks, S.J.; Luc, A.; Bourrain, J.‐L.; Crépy, M.‐N.; Dupas, D.; Frimat, P.; Garnier, R.; Lehucher‐Michel, M.‐P.; et al.
Summary: Background: Occupational allergic contact dermatitis (OACD) is one of the most common occupational skin diseases in developed countries, but data about its temporal trends in incidence remain sparse. Objectives: The aim of this study is to describe OACD trends in terms of industrial activities and main causal agents in France over the period 2001–2010. Materials and methods: Data were collected from the French National Network of Occupational Disease Vigilance and Prevention (RNV3P, Réseau National de Vigilance et de Prévention des Pathologies Professionnelles). All OACD considered probably or certainly associated with an occupational exposure were included in the study. Trends were examined (i) on annual crude numbers of OACD and (ii) on reported odds ratios of OACD calculated using logistic regression models. Results: Overall, 3738 cases of OACD were reported and the mean age of OACD cases was 35 years, 52% being women. The most frequent occupations were hairdressers, health care workers, cleaning staff and masons. The total number of OACD cases remained stable over the study period, but increases in OACD related to isothiazolinones ( P = 0·002), epoxy resins ( P = 0·012) and fragrances ( P = 0·005) were observed. Conversely, decreases were noted for cement compounds ( P = 0·002) and plant products ( P = 0·031). These trends highlight specific sectors and exposures at risk of OACD. Conclusions: Trends in OACD depend on the nature of exposure. Observed decreases were consistent with prevention measures taken during the study period, and the increases observed serve to highlight those areas where preventative efforts need to be made to reduce skin allergies in the workplace.